Meta-analysis of extracorporeal membrane oxygenation in combination with intra-aortic balloon pump vs. extracorporeal membrane oxygenation only in patients with cardiogenic shock due to acute myocardial infarction - Meertens, Max M.; Tichelbäcker, Tobias; Macherey-Meyer, Sascha; Heyne, Sebastian; Braumann, Simon; Nießen, Stephan F.; Baldus, Stephan; Adler, Christoph; Lee, Samuel (Frontiers in Cardiovascular Medicine, 2023)
Background Incidence and mortality of cardiogenic shock (CS) in patients with acute myocardial infarction (AMI) remain high despite substantial therapy improvements in acute percutaneous coronary intervention over the last decades. Unloading the left ventricle in patients with Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) can be performed by using an intra-aortic balloon pumps’ (IABP) afterload reduction, which might be especially beneficial in AMI patients with CS. Objective The objective of this meta-analysis was to assess the effect of VA-ECMO + IABP vs. VA-ECMO treatment on the mortality of patients with CS due to AMI. Methods A systematic literature search was performed using EMBASE, COCHRANE, and MEDLINE databases. Studies comparing the effect of VA-ECMO + IABP vs. VA-ECMO on mortality of patients with AMI were included. Meta-analyses were performed to analyze the effect of the chosen treatment on 30-day/in-hospital mortality. Results Twelve studies were identified by the literature search, including a total of 5,063 patients, 81.5% were male and the mean age was 65.9 years. One thousand one hundred and thirty-six patients received treatment with VA-ECMO in combination with IABP and 2,964 patients received VA-ECMO treatment only. The performed meta-analysis showed decreased mortality at 30-days/in-hospital after VA-ECMO + IABP compared to VA-ECMO only for patients with cardiogenic shock after AMI (OR 0.36, 95% CI 0.30–0.44, P≤0.001). Combination of VA-ECMO + IABP was associated with higher rates of weaning success (OR 0.29, 95% CI 0.16–0.53, P < 0.001) without an increase of vascular access complications (OR 0.85, 95% CI 0.35–2.08, P = 0.72). Conclusion In this meta-analysis, combination therapy of VA-ECMO + IABP was superior to VA-ECMO only therapy in patients with CS due to AMI. In the absence of randomized data, these results are hypothesis generating only.